Analyzing the impact of working capital management on the profitability of Nigerian SMEs - Tsagem, Muhammad Musa; Aripin, Norhani; Ishak, Rokiah (American Scientific Publishers, 2016)
This paper presents an empirical investigation on the working capital management (WCM) and the profitability of under-researched context of small and medium-sized entities in Nigeria.The regression analysis is based on panel data obtained from the financial reports of 311 samples of Nigerian SMEs for the period of 2007– 2013.The results of the study show a statistically significant relationship between account receivables period, cash holdings and cash conversion efficiency with SMEs profitability, proxy by return on assets.The results suggest that SMEs owners/managers need to give more emphasis to efficient management of working capital by optimizing each of the components; account receivables, accounts payable, inventories and cash to improve their profitability, as well as liquidity and financing.In addition, the study contributes to existing literature on the significance of cash holdings and efficient WCM to SMEs profitability for growth and sustainability.